Unconscious processing of happy faces correlates with prosocial tendency but not extraversion - Qian Xu; Qian Xu (Frontiers in Psychology)
Perceiving facial expressions plays a crucial role in face-to-face social interactions. A wealth of studies has revealed the unconscious processing of emotional stimuli, including facial expressions. However, the relationship between the unconscious processing of happy faces and socially oriented personality traits—such as extraversion and prosocial tendency—remains largely unexplored. By pairing backward-masked faces with supraliminally presented faces in both visual fields, we found that the discrimination of visible emotional faces was modulated by the facial expressions of the invisible faces in the opposite visual field. The emotionally consistent condition showed a shorter reaction time (Exp 1) or higher accuracy (Exp 2) than the inconsistent condition. Moreover, the unconscious processing of happy faces was positively correlated with prosocial tendency but not with extraversion personality. These findings shed new light on the adaptive functions of unconscious emotional face processing, and highlight the importance of future investigations into the unconscious processing of extrafoveal happy expression.